Measurement of |Vcb| with B0s→D(*)-s [mu] + [nu] [mu] decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; et al. (Physical review, 2020)
The element |Vcb| of the Cabibbo-Kobayashi-Maskawa matrix is measured using semileptonic B0s decays produced in proton-proton collision data collected with the LHCb detector at center-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. Rates of B0s→D−sμ+νμ and B0s→D*−sμ+νμ decays are analyzed using hadronic form-factor parametrizations derived either by Caprini, Lellouch and Neubert (CLN) or by Boyd, Grinstein and Lebed (BGL). The measured values of |Vcb| are (41.4±0.6±0.9±1.2)×10−3 and (42.3±0.8±0.9±1.2)×10−3 in the CLN and BGL parametrization, respectively. The first uncertainty is statistical, the second systematic, and the third is due to the external inputs used in the measurement. These results are in agreement with those obtained from decays of B+ and B0 mesons. They are the first determinations of |Vcb| at a hadron-collider experiment and the first using B0s meson decays.
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, B. Leverington, H. Malygina, J. Marks, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, L. Witola, A. Zhelezov und weitere 884
Im Titel sind mu und nu als griechische Buchstaben dargestellt
Im Titel sind "cb", "s" und "mu" nach "nu" tiefgestellt
Im Titel sind "0" und "(*)-" hochgestellt
Gesehen am 18.05.2020